Implementasi Metode Qawaid Wa Tarjamah Dan Mauqiuli’rab Santri Pondok Pesantren Al-Risalah Batetangnga Polman - Nurul Afifa; Abd Halim; Kaharuddin Ramli; Darmawati Darmawati; Hamsa Hamsa (Journal on Education, 2024)
This thesis examines the implementation of the Qawaid wa tarjamah and Mauqiul I’rab methods in Qiraatul Kutub learning. The research aims to: (1) Describe the implementation of the Qawaid wa tarjamah and Mauqiul I’rab methods in Qiraatul Kutub learning for students at Al-Risalah Batetangnga Islamic Boarding School, (2) Identify the problems faced in applying these methods, and (3) Assess the impact of these methods on Qiraatul Kutub learning. The research uses a qualitative method, collecting data through direct interviews with structured questions. The data is analyzed and synthesized to create an abstraction of the interview results. Informants are selected using purposive sampling, which involves deliberately choosing informants based on specific criteria, including the head of the school, the female division leader, Qiraatul Kutub teachers, and female students. Data analysis is thematic, with findings organized according to relevant themes The indings show that: (1) The implementation of the Qawaid wa tarjamah and Mauqiul I’rab methods in Qiraatul Kutub learning involves several stages: preparation, execution, and evaluation, (2) The problems encountered in applying these methods are categorized into linguistic and non-linguistic issues, and (3) The impact of the Qawaid wa tarjamah and Mauqiul I’rab methods in Qiraatul Kutub learning includes enhancing and training students to accurately read classical Islamic texts (kitab kuning) according to the rules of Nahwu and Sharaf. The effectiveness and engagement of students are also evidenced by their achievements in MKQ competitions at the district, provincial, and national levels.